UJI AKTIVITAS ANTIKANKER EKSTRAK ETANOL DAUN Rhizopora mucronata TERHADAP SEL MYELOMA - Hartiwi Diastuti; Warsinah Warsinah; Purwati Purwati (Molekul, 2008)
The mangrove plant have been long used the people for traditional medicine to cure various diseases, one of them to cancer therapy. Investigation the anticancer potent of R. mucronata has not been carried yet. This research was aimed to toxicity test of R. mucronta leaves extracts againts Artemia salina Leach, then cytotoxicity test of R. mucronata leave extracts againts Myeloma cancer cells. The extraction of R. mucronata leaves was peformed by maseration with ethanol. The ethanol extracts was partitioned with chloroform, ethylacetate and methanol. The ethanol extracts of R. mucronata leaves respectively was examined their toxicity againts A. salina Leach larv. The toxic exctracts was examined their citotoxicity againts Myeloma cells. The ethanol extract of R. mucronata leaves has toxic character because has LC50 < 1000 mg/mL. Citotoxicity test againts Myeloma cells showed that the chloroform fraction of ethanol extract of R. mucronata leaves have a high activity against Myeloma cell, LC50 value equal to 28,72 mg/mL. Phytochemical study showed that the active fractions contained terpenoid and alkaloid.